Near Infrared Raman Spectroscopy (NIRS): A technique for doping control. Issue 4 (2006) - Guimarães Guimarães, A. E. A. E.; Pacheco Pacheco, M. T. T. M. T. T.; Silveira Jr. Silveira Jr., L. L.; Barsottini Barsottini, D. D.; Duarte Duarte, J. J.; Villaverde Villaverde, A. B. A. B.; Zângaro Zângaro, R. A. R. A.
Abstract : This paper reports the application of near-infrared Raman spectroscopy to detect ephedrine in biological medium. At present time, the doping control for ephedrine in athletes uses the urinalysis by the gas chromatography/mass spectrometry, with main disadvantage the need of collecting urine and the time delay to obtain results. This work aims to develop a noninvasive technique that will allow to evaluate the concentration of the ephedrine in a real time diagnosis. A Raman system composed by a Ti:Saphire laser pumped by an Argon laser was used, operating at the wavelength of 785 nm, with a laser power of 70 mW at sample position. Raman scattered photons were collected by a f/l.8 spectrometer and a N2 -cooled CCD detector. Ephedrine Raman peaks at 1002 and 1603 cm −1 were studied, opening possibility for the identification and quantification of ephedrine. Raman spectra of ephedrine with different concentrations in human urine were taken, and the intensity of the ephedrine peak at 1002 cm −1 was measured as a function of its concentration. It was also studied the Raman spectrum of an urine sample from a Wistar rat, after a subcutaneous inoculation of an ephedrine solution in physiologic serum, at the concentration of 5 mg/ml. It was found that Raman spectroscopy could detect ephedrine in urine at concentrations lower than the doping limit legally permitted by the International Olympic Committee.